Time and transformation in architecture - Lähdesmäki, Tuuli (At the interface/probing the boundaries, 2018)
"Time and Transformation in Architecture, edited by Tuuli Lähdesmäki, explores architecture and the built environment by emphasizing in its theoretical discussions and empirical analysis the dimensions of time, temporality, and transformation--and their relation to human experiences, behavior, and practices."--Provided by publisher.